Extending Play to Critical Media Studies. (November 2014) - Trammell, Aaron; Gilbert, Anne
This essay fosters a dialogue between game studies and critical media studies. By taking Slender Man as its object of study, it argues that play should be understood as a disposition toward media. It suggests a new critical vocabulary for this approach, wherein the moods set by play can be understood as schemes, latitude, or slack. These terms help us to understand the way play is productive of particular affects that set our bodies to motion.